Design and Implementation of Temperature and Humidity Monitoring System Using LPWAN Technology - Danladi, Muhammad Sani; Baykara, Muhammet (International Information and Engineering Technology Association, 2022)
Temperature and humidity monitoring is an integral aspect of human lives and has several applications ranging from greenhouses, laboratories, food industries, server rooms, data centers, and so on. However, the primary technologies that drive these systems suffer from numerous drawbacks such as deployment cost, coverage, and power consumption. This paper aims to employ new and affordable technology, namely low power wide area networks, to implement a temperature and humidity monitoring system (THMS) due to their low cost, low power consumption, and long range in data transmission. A LoRa-based THMS using a Raspberry Pi 3 B+ gateway with a single channel packet forwarder and an Arduino UNO end device with a DHT11 sensor was designed and implemented. After registering the gateway and the end device on The Things Network (TTN), temperature and humidity values of 22.0? and 33.0% were recorded by the Arduino serial monitor and the TTN application server. The above implementation clearly shows that sensor values can be effectively transmitted using LoRa and LoRaWAN over long distances with minimal power consumption. © 2022 International Information and Engineering Technology Association. All rights reserved.
Keywords: data transmission; humidity monitoring; internet of things; long-range; LoRaWAN; LPWAN; temperature